The Transformation of Fiqh and the Implementation of Musyarakah Mutanaqisah as an Instrument of Just Islamic Financing in Indonesia - Fitri Yenti; Syukri Iska; Hospi Burda; Kumaidi Kumaidi; Jasri Waldi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines the fiqh transformation of Musyarakah Mutanaqisah as a Sharia-based financing model in Indonesia by assessing the alignment between fiqh theory, the DSN–MUI fatwa, and banking practices. Although Musyarakah Mutanaqisah is conceptually grounded in partnership, gradual ownership, and risk sharing, its implementation across Islamic banks demonstrates a persistent tendency to resemble conventional credit structures, particularly through fixed rental margins, limited transparency, and weak risk-sharing mechanisms. This research employs a library-based qualitative approach using a normative–maqasidi framework combined with critical–empirical analysis. The findings indicate that the reconstruction of Musyarakah Mutanaqisah must be oriented towards the substantive realisation of Maqasid al-Shariah, particularly justice, public interest, and the protection of wealth. Reformulation is required in contractual structures, accounting systems, Sharia supervision, and the integration of sustainability values. Accordingly, Musyarakah Mutanaqisah holds the potential to evolve into a more equitable, transparent, and welfare-oriented Sharia financing instrument.